The dimensions of work stress among expatriates in Petronas Carigali Sdn Bhd Malaysia (PCSB Malaysia) / Sheikh Mohamad Adzmir Sheikh Ramdzan - Sheikh Ramdzan, Sheikh Mohamad Adzmir (Faculty of Business and Management, 2012)
Work stress becomes a common problem faced by employees in many organizations today. In almost all cases, the responsibilities of expatriates in emerging countries will be larger than they are used to overseeing. It affects employees mental and physical health in the long run affects organization performance. This research studies on three dimensions that influence work stress among the expatriates which are workload, role conflict and interpersonal relationship at work. The expatriates in the company which come from ages range from 25 to 45 years old and from different races, culture and region which consists of Asia, Africa, America, Europe and Middle Eastern. Data is collected through a questionnaire distributed to 50 expatriates in the PCSB Malaysia using stratified sampling. Result of the present study showed that the significant correlation relationship between factors of work stress and work stress. This study also used regression backward analysis in order to identify which factor is most significant to work stress among expatriates in PCSB Malaysia. This study is said to be beneficial to the company especially as they are currently facing high level of job stress. It will help them gain awareness on the main factor of their work stress and in turn help them to manage the condition from getting worse. Recommendations for future research are also having been discussed.